A comunicação profissional-paciente em oncologia: uma compreensão psicanalítica - Bianchini, Daniela Cristina Silva (Universidade do Vale do Rio dos Sinos, 2015)
This dissertation consists of two empirical articles written from the survey conducted about professional-patient communication in oncology. The first study is about the perception of professional-patient communication from the standpoint of cancer patients. Fourteen adult patients who were taken chemotherapy were interviewed. They were in different stages of the disease (seven metastatic) and eight were men. The second study presents the perceptions of professionals who treat cancer patients regarding the communication process. Fourteen different professionals who work with cancer patients were interviewed, including: medicine, psychology, nursing, occupational therapy, dentistry, physiotherapy and nutrition. Both studies were qualitative and exploratory. The instruments used were: a sociodemographic, clinic and professional data questionnaire and a semi-structured interview designed for each group of respondents. The interviews were audio-recorded and transcribed. The data were analyzed in three stages: a) initial reading without judgment (“naive”); b) structural analysis and categorization of content; and c) critical interpretation and discussion. Finally, two independent judges evaluated the interview content as emerging categories. The Kappa index were 0,834 in the first study and 0,842 in the second study, representing strong agreement. Three categories were created and used in both studies: 1) Technical Communication: information provision about diagnosis, treatment and/or prognosis in a technical way oriented for the disease; 2) Technical Communication with Emotional Support: information provision oriented to disease and emotional support; 3) Insufficient Communication: failed communication which leaves the patient with questions and/or unsafe. In study 1, results showed that communication with emotional support contributed improving satisfaction and psychological health during cancer treatment. Negative perceptions regarding communication with health professionals were linked with failures in the exchange of information, sense of emotional detachment and lack of interest on personal aspects. In study 2, results point the importance of interdisciplinary work and the establishment of an effective communication that incorporates the complex demands of cancer patients. Moreover, empathy, providing hope and active listening were identified as essential qualities for effective communication between professional-patient. The findings of both studies may be useful in planning communication strategies to encourage an increase of satisfaction and well-being of patients with cancer.
Keywords: Oncologia; Satisfação do paciente; Qualidade de vida; Oncology; Patient satisfaction; Quality of life; ACCNPQ::Ciências Humanas::Psicologia